Oleosin Cor a 15 is a novel allergen for Italian hazelnut allergic children. Issue 8 (5th July 2021) - Nebbia, Stefano; Lamberti, Cristina; Cirrincione, Simona; Acquadro, Alberto; Abbà, Simona; Ciuffo, Marina; Torello Marinoni, Daniela; Manfredi, Marcello; Marengo, Emilio; Calzedda, Roberta; Monti, Giovanna; Cavallarin, Laura; et al.
Abstract: Background: Hazelnut allergy, which is characterized by symptoms that range from mild to severe, is one of the most common allergies in children throughout Europe, and an accurate diagnosis of this allergy is therefore essential. However, lipophilic allergens, such as oleosins, are generally underrepresented in diagnostic tests. We therefore sought to characterize the IgE reactivity of raw and roasted hazelnut oleosins, using the sera of hazelnut‐allergic pediatric patients. Methods: Raw and roasted hazelnut oil body–associated proteins were analyzed by means of 1D and 2D electrophoresis and MS. Oleosin IgE reactivity was assessed by immunoblotting with the sera of 27 children who have confirmed hazelnut allergies and from 10 tolerant subjects. A molecular characterization of the oleosins was performed by interrogating the C. avellana cv. Jefferson and cv. TGL genomes, and through expression and purification of the recombinant new allergen. Results: A proteomic and genomic investigation allowed two new oleosins to be identified, in addition to Cor a 12 and Cor a 13, in hazelnut oil bodies. One of the new oleosins was registered as a new allergen, according to the WHO/IUIS Allergen Nomenclature Subcommittee criteria, and termed Cor a 15. Cor a 15 was the most frequently immunorecognized oleosin in our cohort. Oleosins resulted to be the only immunorecognized allergens in a subgroup of allergic patients who showed low ImmunoCAP assay IgE values and positive OFC and PbP. Hazelnut roasting resulted in an increase in oleosin immunoreactivity. Conclusion: A novel hazelnut oleosin, named Cor a 15, has been discovered. Cor a 15 could play a role in eliciting an allergic reaction in a subgroup of pediatric patients that exclusively immunorecognize oleosins. The high prevalence of hazelnut oleosin sensitization here reported further confirms the need to include oleosins in routine diagnostic procedures.